Influence of Baffle Block Arrangements and Downstream Weir Slope on Hydraulic Jump and Energy Dissipation on Solid-Roller Bucket Stilling Basins - Abdurrosyid, Jaji; Wibowo, Gurawan Djati; Setiyaningsih, Ika; Adipura, Pembra Juned (Engineering Research: Perspectives on Recent Advances Vol. 7, 2025)
Stilling basin is an alternative water work to reduce the scour, and it is usually supplemented by baffle blocks or defence blocks to increase the effectiveness of the energy dissipater. Baffle walls and blocks are often used to stabilise the jump, decrease its length, and increase the energy dissipation. Performance of baffle walls and blocks in free hydraulic jumps has been studied by numerous researchers. Weir is a water structure built crossing a river to elevate the water level or the channel that will be directed to the irrigation network. The rise in water level due to damming will result in rapid flow downstream. The change of flow from supercritical to subcritical will create a hydraulic jump. To reduce the energy contained in the flow, it is necessary to build an energy dissipater, which is the stilling basin. This study investigates the influence of downstream weir slope and the influence of baffle block arrangement on hydraulic jumps and energy dissipation on the solid-roller bucket. The research was conducted at the Hydraulics Laboratory of the Civil Engineering Department, Faculty of Engineering, UMS. This study used an open flume with dimensions of 30x60x1000 cm with a channel bed slope of 0.0058, an ogee spillway with a downward slope of 1: 4, 2: 4, 3: 4, 4: 4, and a solid-roller bucket stilling basin with baffle blocks of 5/12 R. The shape of the baffle blocks was cubical. The study was conducted on sixteen treatments (downstream slope and placement baffle blocks) with four variations of water discharge, in which the flow turbulence, the length of the whirlpool and energy loss of each discharge were tested. The spillway was designed using maximum discharge to obtain various flows. The findings showed that the increasing flow triggers greater turbulence, the length of the hydraulic jump downstream of the vortex, and a smaller value of the percentage of energy loss. Additionally, the most effective baffle block arrangement in reducing turbulence and hydraulic jumps is the one that is placed at the centre of the curved radius. Moreover, the efficiency of energy loss increases with reduced discharge variation; the treatment without baffle blocks is the most effective. With the same flow rate of the downstream body weir variation, there is an insignificant difference in the flow turbulence and energy loss except for the hydraulic jump length, which is the most effective 4: 4 slope. Further research can explore scouring effects at the downstream vortex, incorporating diverse forms of baffle block shapes, weir slopes, and weir heights for comprehensive analysis.